ZnO Rods with Exposed {100} Facets Grown via a Self-Catalyzed Vapor-Solid Mechanism and Their Photocatalytic and Gas Sensing Properties - Vallejos, Stella; Pizúrová, Naděžda; Gràcia, Isabel; Sotelo-Vazquez, Carlos; Čechal, Jan; Blackman, Chris; Parkin, Ivan; Cané, Carles (ACS applied materials & interfaces, 2016)
We present a new method for vapor deposition of columnar ZnO structures in the form of rods on various substrates without the need for substrate modification with catalyst seed particles and at relatively low temperatures compared to other vapor deposition methods. These structures are used for the photodegradation of stearic acid (C18H36O2) and the photoactivated detection of gases such as carbon monoxide (CO), ethanol (C2H6O), toluene (C7H8), and nitrogen dioxide (NO2) at room temperature, showing improved selectivity compared to tests performed in themoactivated mode.
Keywords: rods; AACVD; photocatalysis; ZnO; gas sensing